The relationship between self-esteem and depression among middle adolescents - Cindy Amalia Sari; Despita Pramesti; Fatma Siti Fatimah; Mulyanti Mulyanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Mental health problems can occur in adolescents due to deviant behavior and curiosity that can negatively affect actions and emotions, even causing depression. Depression causes serious repercussions such as symptoms of hopelessness, high stress, lack of confidence, and even suicidal ideation or attempts. Suicidal ideation and attempts can be exacerbated by self-esteem. Self-esteem in adolescents will affect the feelings that arise, but adolescents often manage in an ineffective way, which can exacerbate depression. Purpose: To determine the relationship between self-esteem and the incidence of depression in middle adolescents. Method: This study used a cross sectional design. Respondents of this study were middle adolescents aged 15-18 years and the sample size was 311 respondents with proportionate stratified random sampling technique. The research instrument used the Rosenberg Self-Esteem Scale (RSES) and Patient Health Questionnaire-9 (PHQ-9) questionnaires. The analysis test used the Spearman Rank test. Results: The results of the Spearman Rank test in the study obtained a p-value = 0.001 (p <0.05) and a Correation Coefficient (r) of -0.287. Conclusion: There is a relationship between self-esteem and the incidence of depression in middle adolescence with a relationship in the low category. Keywords: Adolescents; Depression; Self-esteem.